2014
DOI: 10.1002/hed.23597
|View full text |Cite
|
Sign up to set email alerts
|

Infraclavicular free flap for head and neck reconstruction: Surgical description and early outcomes in 7 consecutive patients

Abstract: ICFF demonstrated similar outcomes compared to conventional fasciocutaneous free flaps. This flap has the potential for common application given its consistent anatomy and donor site advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 25 publications
(75 reference statements)
0
26
0
Order By: Relevance
“…4 Accordingly, our study did not show a difference in the risk of complications related to whether or not the patient had preoperative radiation (P = .202). First, this area is devoid of significant neurovascular structures that could be injured.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…4 Accordingly, our study did not show a difference in the risk of complications related to whether or not the patient had preoperative radiation (P = .202). First, this area is devoid of significant neurovascular structures that could be injured.…”
Section: Discussionmentioning
confidence: 45%
“…Due to the contiguous anatomical relationship between the infraclavicular zone and the ablative site, the color match is usually suitable. 4 In addition, we have found that the infraclavicular perforator is seldom injured during neck dissection. Upper thoracic deformation with loss of pectoralis muscle contour is also avoided (Figure 4).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…To date, there is no consensus regarding the correct nomenclature for this vessel. Some investigators termed it the anterior supraclavicular artery perforator, whereas others have named it the “thoracal branch,” “cervico‐pectoral branch,” or the “anterior supraclavicular vessel.” For consistency and clarity, we have used the term “anterior perforator” and the term “infraclavicular flap” to distinguish it from “supraclavicular” flaps harvested from areas above the clavicle based on the supraclavicular artery.…”
Section: Introductionmentioning
confidence: 99%